Open source BI tools for SMEs: Comparative analysis of Pentaho CE and Knowage CE stacks - Jakimovski, Igor (My University, 2022)
It is well known that Business Intelligence (BI) plays an important role in helping companies in dialing with competition and gain better success in business as many published successful world companies stories show. But how many companies in the domestic market have implemented it? BI is a discipline that transforms data into information that can be used to accelerate the organization's business success. In other words, BI uses data with a bigger historical diapason for comparison with the present ones, for responsible companies people, be able to draw conclusions on what actions to take in the near future or which steps to choose for making better business results or keeping business on the wanted level. This paper makes a proposal while evaluating of two different concrete implemented BI stacks, that could be implemented for small and medium-sized organizations. Evaluation is based on the experience while implementation, testing, and of course manuals of the developers as of the community support.
Keywords: BI, DW, ETL, PDI, TOS, OLAP